Palynomorph Biozonation of the Malawa Formation, Barru Region, South Sulawesi - Zulfiah Zulfiah; Nurhikmah Supardi (Universitas Negeri Gorontalo, 2023)
This study's subject is the Padanglampe traverse in Tanete Riaja, Barru Regency, at coordinates 040 30' 25.26